Prednisone in MOPP chemotherapy for Hodgkin's disease. - Jacobs, C (1976)
High remission rates have been produced by MOPP (mustine, vincristine, procarbazine, and prednisone) chemotherapy in patients with advanced Hodgkin's disease, but the prednisone component has caused adverse effects in patients who have undergone radiotherapy. The remission rates and length of remission were reviewed in 211 patients with Hodgkin's disease who received chemotherapy either with or without prednisone. In contrast to the findings of a British study, there were no significant differences in remission rates or length of remission between patients who had received prednisone and patients who had not. There were differences between the British prospective study and this retrospective one, but it is difficult to know what accounted for the substantial differences in the findings.